A Conceptual Framework for Understanding Sense of Place Dimensions in the Heritage Context - Christin Dameria; Roos Akbar; Petrus Natalivan Indradjati; Dewi Sawitri Tjokropandojo (Journal of Regional and City Planning, 2020)
A thorough knowledge of the sense of place concept is required to understand the relationship between a heritage place and the people doing activities in that place. A good understanding of the human dimension presence is one of the keys to achieving sustainable heritage conservation. Although the concept of sense of place has become part of spatial studies to explain place-people bonding, there is no universal agreement among scholars how to interpret this concept. As a basis for understanding sense of place in a heritage context, this paper proposes a concept of sense of place that was developed from an approach that sees heritage place-people bonding as an attitude. This approach reliably results in a sense of place construction that is comprehensive, unambiguous, and has the potential for further development in later research on conservation behavior. As an attitude concept, sense of place has three dimensions, namely place identity (cognitive component), place attachment (affective component), and place dependence (conative component). Each dimension could be explained by different but interrelated principles. These principles were chosen because they were considered capable of identifying the bonds between people and heritage places that have both tangible and intangible aspects and are influenced by the dimension of time. The relationships between heritage place, sense of place dimensions, and the principles that explain each dimension are arranged in a conceptual framework. This framework can be used as a guideline for heritage researchers to understand the sense of place concept, which seems too abstract and subjective, so that it can be operationalized in research and be applied for the benefit of heritage conservation.Abstrak. Pengetahuan mendalam mengenai konsep sense of place dibutuhkan untuk memahami interaksi yang terjadi antara kawasan pusaka dan individu yang berkegiatan di dalamnya. Pemahaman mengenai kehadiran dimensi manusia adalah salah satu kunci untuk mencapai keberlanjutan pelestarian. Meskipun konsep sense of place telah menjadi bagian dari kajian spasial untuk menjelaskan ikatan tempat-manusia, tetapi belum ada kesepakatan universal tentang bagaimana menyelidiki konsep ini. Sebagai landasan pemahaman dalam konteks pusaka, tulisan ini mengusulkan sebuah konsep sense of place yang disusun berdasarkan pendekatan yang memandang ikatan tempat pusaka-manusia sebagai sebuah konsep sikap. Pendekatan ini andal menghasilkan konstruksi sense of place yang komprehensif, tidak ambigu, dan berpotensi untuk kelak dikembangkan dalam penelitian mengenai perilaku melestarikan. Sebagai sebuah konsep sikap, sense of place memiliki 3 (tiga) dimensi yang terdiri dari place identity (komponen kognitif), place attachment (komponen afektif), dan place dependence (komponen konatif). Masing-masing dimensi dijelaskan dengan prinsip-prinsip yang berbeda, tetapi saling terkait. Prinsip-prinsip tersebut terpilih karena dianggap mampu mengindentifikasi ikatan yang terjadi antara individu dengan lingkungan pusaka yang berwujud dan tak berwujud, serta dipengaruhi oleh dimensi waktu. Hubungan yang terbentuk antara kawasan pusaka, ketiga dimensi sense of place, dan prinsip-prinsip yang menjelaskan setiap dimensi, disusun dalam sebuah kerangka konseptual. Kerangka konseptual ini dapat menjadi panduan bagi para peneliti pusaka untuk memahami konsep sense of place yang terkesan abstrak dan subjektif sehingga kelak dapat dioperasionalkan dalam penelitian dan diaplikasikan untuk kepentingan pelestarian kawasan pusaka.Kata kunci. Place attachment, place dependence, place identity, pusaka, sense of place.